Macroeconomic fluctuations and firm entry: theory and evidence - Vivien Lewis (National Bank of Belgium, 2006)
This paper studies the behaviour of firm entry and exit in response to macroeconomic shocks. We formulate a dynamic stochastic general equilibrium model with an endogenous number of producers. From the calibrated model, we derive a minimum set of robust sign restrictions to identify four kinds of macroeconomic shocks in a vector autoregression, namely supply, demand, monetary and entry cost shocks. The variables entering the VAR are output, inflation, the nominal interest rate, profits and firm entry. The response of firm entry to the various shocks is freely estimated. Our main finding is that entry responds significantly to all types of shocks. The results also show a crowding-in of firm entry following an exogenous rise in demand, consistent with the effect of a consumption preference shock predicted by the model
Keywords: E30; E32; 330; firm entry; VAR; business cycles; Markteintritt; Marktaustritt; Marktstruktur; VAR-Modell; Konjunktur; Gleichgewichtstheorie